Structural network alterations in patients with nasopharyngeal carcinoma after radiotherapy: A 1-year longitudinal study - Zhang, Xinyuan; Pan, Jie; Lin, Yuhao; Fu, Gui; Xu, Pu; Liang, Jiahui; Ye, Chenfei; Peng, Jie; Lv, Xiaofei; Yang, Yadi; Feng, Yanqiu (Frontiers in Neuroscience, 2022)
This longitudinal study explored the changed patterns of structural brain network after radiotherapy (RT) in patients with nasopharyngeal carcinoma (NPC). DTI data were gathered from 35 patients with NPC at four time points: before RT (baseline), 0~3 (acute), 6 (early-delayed), and 12 months (late-delayed) after RT. The graph theory was used to characterize the dynamic topological properties after RT and the significant changes were detected over time at the global, regional and modular levels. Significantly altered regional metrics (nodal efficiency and degree centrality) were distributed in the prefrontal, temporal, parietal, frontal, and subcortical regions. The module, that exhibited a significantly altered within-module connectivity, had a high overlap with the default mode network. In addition, the global, regional and modular metrics showed a tendency of progressive decrease at the acute and early-delayed stages, and a partial/full recovery at the late-delayed stage. This changed pattern illustrated that the radiation-induced brain damage began at the acute reaction stage and were aggravated at the early-delayed stage, and then partially recovered at the late-delayed stage. Furthermore, the spearman's correlations between the abnormal nodal metrics and temporal dose were calculated and high correlations were found at the temporal (MTG.R and HES.L), subcortical (INS.R), prefrontal (ORBinf.L and ACG.L), and parietal (IPL.R) indicating that these regions were more sensitive to dose and should be mainly considered in radiotherapy treatment plan.